2003
DOI: 10.1046/j.1464-5491.2003.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of digital imaging, retinal photography and optometrist examination in screening for diabetic retinopathy

Abstract: Both manual grading methods produced similar results whether using a one- or two-field protocol. Technical failures rates, and hence need for recall, were lower with digital imaging. One-field grading of fundus photographs appeared to be as effective as two-field. The optometrists achieved the lowest sensitivities but reported no technical failures. Automated grading of retinal images can improve efficiency of resource utilization in diabetic retinopathy screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
105
3
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(120 citation statements)
references
References 28 publications
5
105
3
7
Order By: Relevance
“…Similar studies in countries like the UK had clinical practice as part of their curriculum. The studies showed sensitivity between 72% and 76% and specificity between 77% and 99% (Hulme et al, 2002;Olson et al, 2003;Prasad et al, 2001). These results were somewhat poorer in sensitivity, but better in specificity than our results.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Similar studies in countries like the UK had clinical practice as part of their curriculum. The studies showed sensitivity between 72% and 76% and specificity between 77% and 99% (Hulme et al, 2002;Olson et al, 2003;Prasad et al, 2001). These results were somewhat poorer in sensitivity, but better in specificity than our results.…”
Section: Discussioncontrasting
confidence: 56%
“…It has also been shown that assessment of red-free retinal images is better than retinal slit-lamp examination, but the best results were achieved by grading colour images (Olson et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Other assessment systems in published reports have combined field and 14,15 or image definition alone 16 and usually do not address whether the fovea can be visualised as an independent criterion. We demonstrate the most common cause of an ungradeable image was the fovea not being adequately visualised, whether mydriasis was used or not.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a dilated fundus examination by a trained examiner, use non-mydriatic (or mydriatic) photography with adequate sensitivity, specificity and low technical failure rate to detect presence of DR (Systematic review of diagnostic accuracy studies 20 and individual diagnostic accuracy studies [22][23][24][25][26] ).…”
mentioning
confidence: 99%